Induced resistance to Fusarium wilt of banana caused by Tropical Race 4 in Cavendish cv Grand Naine bananas after challenging with avirulent Fusarium spp. (2022)
In the last century, Fusarium wilt of banana (FWB) destroyed the banana cultivar Gros Michel. The Cavendish cultivars saved the global banana industry, and currently they dominate global production (~50%) and the export trade (~95%). However, a new strain called Tropical Race 4 (TR4) surfaced in the late 1960's, spread globally and greatly damages Cavendish plantations as well as manifold local varieties that are primarily grown by small holders. Presently, there is no commercially available replacement for Cavendish and hence control strategies must be developed and implemented to manage FWB. Here, we studied whether it is possible to induce resistance to TR4 by pre-inoculations with different Fusarium spp. Only pre-treatments with an avirulent Race 1 strain significantly reduced disease development of TR4 in a Cavendish genotype and this effect was stable at various nutritional and pH conditions. We then used transcriptome analysis to study the molecular basis of this response. Several genes involved in plant defence responses were up-regulated during the initial stages of individual infections with TR4 and Race 1, as well as in combined treatments. In addition, a number of genes in the ethylene and jasmonate response pathways as well as several gibberellin synthesis associated genes were induced. We observed upregulation of RGA2 like genes in all treatments. Hence, RGA2 could be a key factor involved in both R1 and TR4 resistance. The data support the hypothesis that activating resistance to Race 1 in Cavendish bananas affects TR4 development and provide a first insight of gene expression during the interaction between various Fusarium spp. and banana.